The nucleosome (histone-DNA complex) is the TLR9-specific immunostimulatory component of Plasmodium falciparum that activates DCs. - Nagaraj M Gowda; Xianzhu Wu; D Channe Gowda (PLoS ONE, 2011)
The systemic clinical symptoms of Plasmodium falciparum infection such as fever and chills correspond to the proinflammatory cytokines produced in response to the parasite components released during the synchronized rupture of schizonts. We recently demonstrated that, among the schizont-released products, merozoites are the predominant components that activate dendritic cells (DCs) by TLR9-specific recognition to induce the maturation of cells and to produce proinflammatory cytokines. We also demonstrated that DNA is the active constituent and that formation of a DNA-protein complex is essential for the entry of parasite DNA into cells for recognition by TLR9. However, the nature of endogenous protein-DNA complex in the parasite is not known. In this study, we show that parasite nucleosome constitute the major protein-DNA complex involved in the activation of DCs by parasite nuclear material. The parasite components were fractionated into the nuclear and non-nuclear materials. The nuclear material was further fractionated into chromatin and the proteins loosely bound to chromatin. Polynucleosomes and oligonucleosomes were prepared from the chromatin. These were tested for their ability to activate DCs obtained by the FLT3 ligand differentiation of bone marrow cells from the wild type, and TLR2(-/-), TLR9(-/-) and MyD88(-/-) mice. DCs stimulated with the nuclear material and polynucleosomes as well as mono- and oligonucleosomes efficiently induced the production of proinflammatory cytokines in a TLR9-dependent manner, demonstrating that nucleosomes (histone-DNA complex) represent the major TLR9-specific DC-immunostimulatory component of the malaria parasite nuclear material. Thus, our data provide a significant insight into the activation of DCs by malaria parasites and have important implications for malaria vaccine development.